Impact of Information Technology, Clinical Resource Constraints, and Patient-Centered Practice Characteristics on Quality of Care - JongDeuk Baek; Robert L. Seidman (SAGE Publishing, 2015)
Objective: Factors in the practice environment, such as health information technology (IT) infrastructure, availability of other clinical resources, and financial incentives, may influence whether practices are able to successfully implement the patient-centered medical home (PCMH) model and realize its benefits. This study investigates the impacts of those PCMH-related elements on primary care physicians' perception of quality of care. Methods: A multiple logistic regression model was estimated using the 2004 to 2005 CTS Physician Survey, a national sample of salaried primary care physicians (n = 1733). Results: The patient-centered practice environment and availability of clinical resources increased physicians' perceived quality of care. Although IT use for clinical information access did enhance physicians' ability to provide high quality of care, a similar positive impact of IT use was not found for e-prescribing or the exchange of clinical patient information. Lack of resources was negatively associated with physician perception of quality of care. Conclusion: Since health IT is an important foundation of PCMH, patient-centered practices are more likely to have health IT in place to support care delivery. However, despite its potential to enhance delivery of primary care, simply making health IT available does not necessarily translate into physicians' perceptions that it enhances the quality of care they provide. It is critical for health-care managers and policy makers to ensure that primary care physicians fully recognize and embrace the use of new technology to improve both the quality of care provided and the patient outcomes.